ANALISIS KOMPARASI PERFORMA JARINGAN KOMPUTER PADA IMPLEMENTASI IPv4 dan IPv6 - Ahmad Tantoni; Mohammad Taufan Asri Zaen; Sofiansyah Fadli (LPPM STMIK Lombok, 2018)
Routers have important functions in the network, especially the internet. Routers can connect several network segments so that they can communicate with other users even though they are separated by a great distance (Sofana, 2013). IPv4 was originally a 32-bit binary number that was used to identify hosts on the network, after successful use by internet users then a new problem arises where IPv4 cannot accommodate Internet users in the future because it runs out of IPv4 addresses. Then IPv6 was created with the aim to provide more addressing than IPv4 (Sugeng, 2015). The problem is seen from the difference in the bit width between IPv4 and IPv6 whether it affects the CPU performance of the computer and the performance of data sent, average speed on the network. Then there will be research on the comparative performance of the CPU load and the performance of the data sent, the average speed of the computer network on the implementation of IPv4 and IPv6 using Passmark Advance Network Test. So that it can provide an overview of the results of the comparison of IPv4 and IPv6 QoS that are better than the 3 parameters tested with TCP and UDP protocols